Scaffolding speaking tasks using videoblog portfolio in an ESL classroom - Shuib, Asyraf; Ismail, Lilliati; Abdul Manaf, Umi Kalthom (Horizon Research Publishing, 2020)
Video blogging (vlogging) was chosen in this study as a language learning tool. The idea of studying video blogging stems from Vygotsky’s socio-constructivism theory and Siemens’ theory of networking, connectivism. The theories underpinned the study and were applied in a project based on instruction, which gave emphasis on student-centred learning. Assuming the roles of instructional designers, the researchers initiated this project to address instructional needs by integrating technological media to facilitate learners’ speaking fluency development. This case study explored the network and collaborative traits that vlogging could bring in learning a second language. Data was collected from field observations, a qualitative document and a focus group interview. The researchers then analysed the qualitative data to identify the scaffolding techniques used by the participants of the study. The researchers coded and clustered the scaffolding techniques into themes based on two types of scaffoldings; (i) sensory scaffoldings, and (ii) interactive scaffoldings. The findings show that learners employed scaffolding techniques to facilitate learning amongst peers and knowledgeable others throughout the vlog portfolio project.